2009
DOI: 10.1007/s10800-009-9796-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polarization type on properties of Ni–W nanocrystalline electrodeposits

Abstract: Nickel-tungsten nanocrystalline coatings were electrodeposited from a Watts type bath onto a copper substrate, at different current densities selected from activation, mixed and diffusion controlled regions in the cathodic scan plot at room temperature. The results confirm that tungsten codeposition proceeds via the adsorption and reduction of complexes produced in the bulk of solution. The coatings obtained were single phase solid solutions and their grain sizes increased with current density. A cauliflower-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…The first time constant, which appears as a small capacitive loop at very high frequencies, belongs to the formation and adsorption of a surface oxide film. This loop is also observed in Ni-W electrodeposition according to the results obtained by Kabi et al [12]. The second time constant, which appears as a large capacitive loop at medium frequencies, results from double layer capacitance parallel to charge transfer resistance.…”
Section: Electrochemical Aspects Of Depositionsupporting
confidence: 79%
See 1 more Smart Citation
“…The first time constant, which appears as a small capacitive loop at very high frequencies, belongs to the formation and adsorption of a surface oxide film. This loop is also observed in Ni-W electrodeposition according to the results obtained by Kabi et al [12]. The second time constant, which appears as a large capacitive loop at medium frequencies, results from double layer capacitance parallel to charge transfer resistance.…”
Section: Electrochemical Aspects Of Depositionsupporting
confidence: 79%
“…Regarding the mechanism of tungsten deposition proposed by Imanaga et al [13], the high-frequency capacitive loop observed on the Nyquist plots can be an evidence for intermediate tungsten oxide formation [12]. On the other hand, the capacitive loop which appears at low frequencies should be due to the slow bulk diffusion of electrochemical active species, which participate in electrodeposition process [12].…”
Section: Electrochemical Aspects Of Depositionmentioning
confidence: 92%
“…This indicates complete dissolution of elements in the cobalt matrix and a single phase solid solution would occur. Similar results were also reported by other researchers [16,[24][25][26]. By increasing current density the amount of iron content increased.…”
Section: Structural Characterizationsupporting
confidence: 91%
“…At first, we decided the composition of bulk amorphous Ni-W alloy from the reported data 9,[12][13][14][15][16][17][18][19] with our present results. Figure 1 shows the relationship between grain size and W-concentration in electrodeposited Ni-W alloys.…”
Section: Methodsmentioning
confidence: 91%
“…[9] T. J. Rupert et al [12] K.R. Sriraman et al [13] S. Kabi et al [14] A. Giga et al [15] H. Cesiulis et al [16] C.A. Schuh et al [17] T. Yamasaki [18] H. Somekawa et al [19] 0.035 at%/mm in the bulk specimen.…”
Section: Methodsmentioning
confidence: 99%